2007
DOI: 10.1021/jp074867w
|View full text |Cite
|
Sign up to set email alerts
|

Multistep Crystal Nucleation:  A Kinetic Study Based on Colloidal Crystallization

Abstract: Crystallization via an amorphous precursor, the so-called multistep crystallization (MSC), plays a key role in biomineralization and protein crystallization. MSC has attracted much attention in the past decade, but a quantitative understanding of it has so far not been available. The major challenge is that the kinetics governing the nucleation of crystals occurring in the metastable amorphous precursor remains unclear. In this study, the kinetics of MSC is addressed experimentally. Most importantly, a mathema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 31 publications
(55 reference statements)
4
38
0
Order By: Relevance
“…(b) In agreement with theory [18], molecular dynamics simulations [19], and colloid experiments [20][21][22], recent investigation relying on the PFC model have shown that at large supersaturations/undercoolings crystal nucleation is a two-step process, in which an amorphous precursor assists the formation of the crystalline phase [4,6,8].…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…(b) In agreement with theory [18], molecular dynamics simulations [19], and colloid experiments [20][21][22], recent investigation relying on the PFC model have shown that at large supersaturations/undercoolings crystal nucleation is a two-step process, in which an amorphous precursor assists the formation of the crystalline phase [4,6,8].…”
Section: Introductionsupporting
confidence: 63%
“…Apparently, this phenomenon is highly relevant not only for colloids [18,21,22,37], but for such simpler systems as the Lennard-Jones fluid [18] and the hard sphere system [19], raising the possibility that the presence of an amorphous precursor might be a general feature of crystal nucleation in highly undercooled or supersaturated liquids. In this subsection, we investigate the structural aspects of this process within the framework of the PFC model.…”
Section: Structural Aspects Of Two-step Homogeneous Nucleation In Higmentioning
confidence: 99%
“…Nevertheless, this assumption has been challenged by evidence from simulations [10][11][12] and experiments. [13][14][15] The key point of this evidence is that in crystallization, nucleation begins with a metastable structure and the stable structure is reached subsequently. This picture is consistent with the prediction of the Ostwalds rule.…”
mentioning
confidence: 99%
“…This suggests that a TiCl 4 posttreatment can improve the binding of the dye. 19) In addition, a decrease in surface area results from the reduction of the specific area states that are inaccessible to the dye due to steric constraints. 20) The amount of dye loading with 15% acetic acid is decreased slightly because too much reduction of pore size can offset the performance of acetic acid.…”
Section: Characterization Of Tio 2 Layermentioning
confidence: 99%